Original paperThe adherence and illness perception of patients diagnosed with asthma or chronic obstructive pulmonary disease treated with polytherapy using new generation Cyclohaler - Olszanecka-Glinianowicz, Magdalena; Almgren-Rachtan, Agnieszka (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: The factors influencing adherence of patients diagnosed with asthma and chronic obstructive pulmonary disease (COPD) include the complexity of the therapy, fear of side effects of drugs, method of taking the drug, dosage regimen, polypharmacy, adverse events, knowledge about the essence of the disease and its complications, illness perception and priorities in life, training on the use of the inhaler, the duration of treatment, social support, and drug availability. Aim : To assess the adherence of patients diagnosed with asthma and COPD treated with polytherapy with fluticasone propionate and formoterol fumarate using the Fantasmino inhaler in relation to primary diagnosis and illness perception as well as patients’ and doctors’ opinion about this form of therapy. Material and methods : A questionnaire survey covering adherence, illness perception and opinion about polytherapy using new generation Cyclohaler performed by pulmonologists, allergologists and general practitioners in 3,618 patients with asthma and 2,602 with COPD. Results : On visit 1, a lower adherence rate was observed in COPD than in the asthma group (72.0% vs. 61.5%; p < 0.01). During the observation, the adherence rate increased significantly in the COPD group, only (61.5% vs. 73.0%; p < 0.01). A negative correlation between total MMAS-8 and BIPQ scores was observed in both study groups (R = –0.15; p < 0.001 and R = –0.24; p < 0.001, respectively). During the observation, a percentage of patients who believed that the administration of the two drugs in a single inhaler considerably facilitates their use increased significantly in both study groups. In addition, an increased percentage of doctors believed that this therapeutic option facilitated education of patients and decreased the number of errors made by the patients. Conclusions .: The illness perception, younger age, disease duration and severity are predictors of adherence to treatment with fluticasone propionate and formoterol fumarate using the Fantasmino inhaler among patients with asthma and COPD. The positive opinion of patients and doctors about administration of fluticasone propionate and formoterol fumarate using the Fantasmino inhaler increased during observation.